Visual outcome after correcting the refractive error of large pupil patients with wavefront-guided ablation - Khalifa MA; Allam WA; Shaheen MS (Clinical Ophthalmology, 2012)
Mounir A Khalifa,1,2 Waleed A Allam,1,2 Mohamed S Shaheen2,31Ophthalmology Department, Tanta University Eye Hospital, Tanta, Egypt; 2Horus Vision Correction Center, Alexandria, Egypt; 3Ophthalmology Department, Alexandria University, Alexandria, EgyptPurpose: To investigate the efficacy and predictability of wavefront-guided laser in situ keratomileusis (LASIK) treatments using the iris registration (IR) technology for the correction of refractive errors in patients with large pupils.Setting: Horus Vision Correction Center, Alexandria, Egypt.Methods: Prospective noncomparative study including a total of 52 eyes of 30 consecutive laser refractive correction candidates with large mesopic pupil diameters and myopia or myopic astigmatism. Wavefront-guided LASIK was performed in all cases using the VISX STAR S4 IR excimer laser platform. Visual, refractive, aberrometric and mesopic contrast sensitivity (CS) outcomes were evaluated during a 6-month follow-up.Results: Mean mesopic pupil diameter ranged from 8.0 mm to 9.4 mm. A significant improvement in uncorrected distance visual acuity (UCDVA) (P < 0.01) was found postoperatively, which was consistent with a significant refractive correction (P < 0.01). No significant change was detected in corrected distance visual acuity (CDVA) (P = 0.11). Efficacy index (the ratio of postoperative UCDVA to preoperative CDVA) and safety index (the ratio of postoperative CDVA to preoperative CDVA) were calculated. Mean efficacy and safety indices were 1.06 ± 0.33 and 1.05 ± 0.18, respectively, and 92.31% of eyes had a postoperative spherical equivalent within ±0.50 diopters (D). Manifest refractive spherical equivalent improved significantly (P < 0.05) from a preoperative level of −3.1 ± 1.6 D (range −6.6 to 0 D) to −0.1 ± 0.2 D (range −1.3 to 0.1 D) at 6 months postoperative. No significant changes were found in mesopic CS (P ≥ 0.08), except CS for three cycles/degree, which improved significantly (P = 0.02). Magnitudes of primary coma and trefoil did not change significantly (P ≥ 0.34), with a small but statistically significant increase in primary spherical aberration.Conclusion: Wavefront-guided LASIK provides an effective correction of low to moderate myopia or myopic astigmatism in large pupil patients without deterioration of visual quality.Keywords: large pupil, wavefront, LASIK